2015
DOI: 10.1158/1078-0432.ccr-14-0986
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Model System to Evaluate Local Recurrence in Osteosarcoma and Assessment of the Effects of Bone Morphogenetic Protein-2

Abstract: Purpose: It is increasingly relevant to better define what constitutes an adequate surgical margin in an effort to improve reconstructive longevity and functional outcomes following osteosarcoma surgery. In addition, nonunion remains a challenging problem in some patients following allograft reconstruction. Bone morphogenetic protein-2 (BMP-2) could enhance osseous union, but has been historically avoided due to concerns that it may promote tumor recurrence.Experimental Design: An orthotopic xenograft murine m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The exogenous application of BMP-2 to the surgical site following tumor excision does not increase the risk of local recurrence. 39 Furthermore, a recent study by Gill et al using xenografted OSA indicated that the addition of BMP-2 did not increase the risk of lung metastasis. 40 However, the major limitation of all the above studies was that the observations were mainly based on the subcutaneous model system.…”
Section: Introductionmentioning
confidence: 97%
“…The exogenous application of BMP-2 to the surgical site following tumor excision does not increase the risk of local recurrence. 39 Furthermore, a recent study by Gill et al using xenografted OSA indicated that the addition of BMP-2 did not increase the risk of lung metastasis. 40 However, the major limitation of all the above studies was that the observations were mainly based on the subcutaneous model system.…”
Section: Introductionmentioning
confidence: 97%
“…The incidence of osteosarcoma in the world is approximately 3–4 per million new cases [3]. At present, the commonly used clinical treatment methods include systemic chemotherapy and local control surgery [4]. With the advancement of surgery and the introduction of neoadjuvant chemotherapy, great improvements have been made in the clinical response and long-range survival rate of osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Rici et al treated canine mesenchymal stem cells with BMP‐2 and then added them to cultures of canine osteosarcoma cells and their findings suggested that treatment of bone marrow cells with rhBMP‐2 may have therapeutic potential for osteosarcoma treatment . Furthermore, Park et al found that treatment with BMP‐2 combined with a MEK inhibitor inhibited the proliferation of MG‐63 osteosarcoma cells, and Geller et al reported that the application of BMP‐2 did not increase local recurrence of osteosarcoma in an orthotopic xenograft murine model …”
mentioning
confidence: 99%